Genistein Ameliorated Vascular Endothelial Growth Factor-A (VEGF-A) and Estrogen Receptor-Alpha (ER-α) in Endometriosis Mice Model, In Vivo and In Silico - Sutrisno Sutrisno; Maharani Maharani (The Scientific World Journal)
Endometriosis (EM) is a gynecological disorder that causes morbidity in women and is characterized by endometrial tissue in the uterus cavity. This study investigated the mechanism of genistein in the VEGF-A and ER-α expression through in vivo and in silico approaches. An in vivo study was conducted by thirty-six mice that were divided into six groups including control, EM, and EM treatment with genistein with the doses of 1.3, 1.95, 2.6, and 3.25 mg/day for 14 days. Peritoneal tissues with lesions were collected and analyzed by immunohistochemistry to measure the VEGF-A and ER-α expression. The data were analyzed using a statistical approach using one-way ANOVA followed by Tukey HSD test with a significant value p<0.05. In silico study was conducted for investigating the inhibition mechanism of genistein in VEGF-A and ER-α protein. Genistein significantly reduced the VEGF-A and ER-α expression with the optimum dose of 3.25 mg/day. Molecular docking showed that genistein inhibited VEGF-A in several active site residues of VEGF-A, also blocked the ER-α protein in estradiol binding sites. This study concluded that genistein prevented endometriosis by performing the antiangiogenic activity and showed a similar function to estradiol.